The (a -b)2formula is offered to uncover the square of a binomial.This (a -b)2formula is just one of the algebraic identities. This formula is also known together the formula for the square of the difference of two terms. The(a -b)2formula is used to factorize some special varieties of trinomials. In this formula, wefind the square the the difference of 2 terms and also thensolve it through the assist of algebraic identity. Let united state learn an ext about(a -b)2formula in addition to solved instances in the complying with section.

You are watching: (a-b)2

## What Is(a-b)^2 Formula?

The (a -b)2formula is also widely well-known as the square the the difference in between the 2 terms. This formula is sometimes used to factorizethe binomial. To discover the formula of(a -b)2, us will simply multiply (a -b)(a -b).

(a -b)2=(a -b)(a -b)

= a2-ab -ba + b2

= a2-2ab + b2

Therefore,(a -b)2formula is:

(a -b)2= a2-2ab + b2

### Proof of(a − b)2Formula

Let united state consider(a - b)2as the area the a square with size (a - b). In the above figure, the biggestsquare is shown with areaa2.

To prove that (a -b)2= a2-2ab + b2, think about reducing the size of every sides by element b, and it i do not care a - b. In the number above, (a - b)2is shown by the blue area.Now subtract the vertical and horizontal strips that have the area a×b. Removing a × btwice will alsoremovethe overlapping square at the bottom ideal cornertwice hence add b2. Top top rearranging the data we have(a − b)2= a2− ab − abdominal + b2. Hence this proves the algebraic identity(a − b)2= a2− 2ab + b2

Want to find complicated math options within seconds?

Use our cost-free online calculator to solve challenging questions. With bsci-ch.org, uncover solutions in an easy and basic steps.

Book a complimentary Trial Class

## Examples on(a**-**b)^2 Formula

Let usconsider few illustrations based onthe (a**-**b)^2 formula in this solved instances section.

**Example 1:**Find the worth of (x -2y)2by using(a -b)2formula.

**Solution:**

To find: The value of (x - 2y)2.Let us assume that a = x and also b = 2y.We will substitute these values in (a -b)2formula:(a -b)2= a2-2ab + b2(x-2y)2= (x)2-2(x)(2y) + (2y)2= x2- 4xy + 4y2

**Answer:(x -2y)2= x2- 4xy + 4y2.**

**Example 2:**Factorize x2- 6xy + 9y2by using(a -b)2formula.

**Solution:**

To factorize: x2- 6xy + 9y2.We deserve to write the offered expression as:(x)2-2 (x) (3y) + (3y)2.Using(a -b)2formula:a2-2ab + b2=(a -b)2Substitute a = x and also b = 3y in this formula:(x)2-2 (x) (3y) + (3y)2. = (x - 3y)2

**Answer:x2- 6xy + 9y2= (x - 3y)2.**

**Example 3:**Simplify the complying with using (a-b)2 formula.

(7x - 4y)2

**Solution:**

a = 7x and also b = 4yUsing formula (a - b)2 =a2 - 2ab + b2(7x)2 - 2(7x)(4y) + (4y)249x2 - 56xy + 16y2

**Answer:**(7x - 4y)2=49x2 - 56xy + 16y2.

## FAQs ~ above (a -b)^2Formula

### What Is the expansion of (a -b)2Formula?

(a -b)2formula is review as a minusb whole square. Its expansion is to express as(a - b)2 =a2 - 2ab + b2

### What Is the(a -b)2Formula in Algebra?

The (a -b)2formula is also known as one of the importantalgebraic identities. The is review as a minusb whole square. Its (a -b)2formula is express as(a - b)2 =a2 - 2ab + b2

### How To leveling Numbers Usingthe(a -b)2Formula?

Let us know the use of the (a -b)2formula with the aid of the complying with example.**Example:**Find the worth of (20- 5)2using the (a -b)2formula.To find:(20- 5)2Let united state assume that a = 20 and b = 5.We will substitute these in the formula of(a- b)2.(a - b)2 =a2 - 2ab + b2(20-5)2= 202- 2(20)(5) + 52=400-200 + 25=225**Answer:**(20-5)2= 225.

### How To usage the(a -b)2Formula offer Steps?

The following steps are adhered to while using(a -b)2formula.

See more: What Travels The World But Stays In The Corner But Travels Around The World?